2019
DOI: 10.1063/1.5123462
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant tumor microvesicles attach to endothelial cells on biochips under microfluidic flow

Abstract: Tumour patients are at a high risk of venous thromboembolism (VTE) and the mechanism by which this occurs may involve tumour derived microvesicles (MV). Previously, it has been shown that tumour MV become attached to endothelial cells in static conditions. To investigate whether this process occurs under physiologically relevant flow rates, tumour MV were perfused across a microfluidic device coated with growing human umbilical endothelial cells (HUVECs).Cell lines were screened for their ability to form tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…The increased PCA of the HUVECs was further increased in the presence of doxorubicin treatment of the tumour spheroids. We have previously shown that tumour MP are able to bind to endothelial cells, transfer and increase the PCA of endothelial cells in static and flow conditions [27,28], and here we demonstrate that the incubation of a cytotoxic agent with the tumour spheroids further increased the PCA of endothelial cells when exposed to tumour MP in flow conditions. The average loss of MP over the HUVEC layer was similar but slightly enhanced in the presence of DOX compared to media alone.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The increased PCA of the HUVECs was further increased in the presence of doxorubicin treatment of the tumour spheroids. We have previously shown that tumour MP are able to bind to endothelial cells, transfer and increase the PCA of endothelial cells in static and flow conditions [27,28], and here we demonstrate that the incubation of a cytotoxic agent with the tumour spheroids further increased the PCA of endothelial cells when exposed to tumour MP in flow conditions. The average loss of MP over the HUVEC layer was similar but slightly enhanced in the presence of DOX compared to media alone.…”
Section: Discussionsupporting
confidence: 71%
“…MP were analysed immediately, directly from samples of effluent media which was centrifuged to remove any larger cell debris (1000× g, 5 min) prior to addition of antibodies. Samples of supernatant (50 μL) were incubated with 5 μL of anti-TF: FITC (Bio-Rad, clone CLB/TF-5) for 30 min then analysed by flow cytometry by adding an equal volume of Accucheck beads (Invitrogen, UK) and 150 μL of 0.2 μm-filtered sterile PBS [27,28]. A flow cytometer (BD FACSCalibur) was set up with Megamix SSC beads (Biocytex, France) that were used to define an MP gate from 200-500 nm according to side-scatter characteristics of the beads following the International Society of Thrombosis and Haemostasis current recommendation for standardisation of MP measurement by flow cytometry [29].…”
Section: Flow Cytometrymentioning
confidence: 99%
“…In Figure 8, it can be observed that 40% of microfluidic devices have been validate using body fluids taken from healthy donors or real patients, representing a good per centage of the total microfluidics-based studies. Among these works, most use immu noaffinity-based devices to capture vesicles, increasing the difference already noted i [87,173] Serum [122,168] Cell culture [109,113,122,[155][156][157][158][160][161][162][164][165][166][167]172,[174][175][176][177]179,180,[196][197][198][199][200] 24…”
Section: Are Microfluidic Devices For Ev Isolation Ready For Clinical...mentioning
confidence: 99%
“…Uptake of MVs by target cells is largely mediated by receptors that interact with the universal molecules present in the MV membrane, such as lipids and specific peptides ( Figure 1 ). MVs range between 100 and 1000 nm in diameter and are therefore easily internalized into target cells by receptor-mediated endocytosis or phagocytosis [ 60 , 71 ]. MVs have been shown to deliver cargo and elicit strong cellular and humoral immune responses [ 58 ].…”
Section: The Biogenesis Of Mvsmentioning
confidence: 99%